In memoriam: James Bailey (September 28, 1929 – July 20, 2020) - Grigori Utgof (Slavica Revalensia)
This is an obituary for Prof. James Bailey of the University of Wisconsin-Madison, a distinguished expert in versification studies, an explorer of Russian folklore, and a scholar known for his coining a frequently quoted synonym for a linguo-statistical method to the study of verse: “the Russian method.”